2002
DOI: 10.1002/cyto.10080
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial and nonmitochondrial reduction of MTT: Interaction of MTT with TMRE, JC‐1, and NAO mitochondrial fluorescent probes

Abstract: Background: Bioreduction of water-soluble tetrazolium salts (e.g., MTS, XTT, and MTT) to their respective formazans is generally regarded as an indicator of cell "redox activity." The reaction is attributed mainly to mitochondrial enzymes and electron carriers. However, MTT reduction may also be catalyzed by a number of other nonmitochondrial enzymes. The goal of this work was to establish the sites of MTT reduction in intact HepG2 human hepatoma cells in culture. Methods: In order to establish the subcellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
156
0
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(163 citation statements)
references
References 32 publications
2
156
0
5
Order By: Relevance
“…Bernas and Dobrucki (2002) have also shown that MTT reduction may be catalyzed by a number of nonmitochondrial enzymes. In their study, only 25-45% of MTT-formazan was associated with mitochondria after 25 min of incubation and most MTT-formazan deposits were not coincident with mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Bernas and Dobrucki (2002) have also shown that MTT reduction may be catalyzed by a number of nonmitochondrial enzymes. In their study, only 25-45% of MTT-formazan was associated with mitochondria after 25 min of incubation and most MTT-formazan deposits were not coincident with mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Oocyte reduction potential was assessed by use of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide (MTT), a water-soluble tetrazolium salt that precipitates as a colored formazan upon reduction. 26 Groups of 25 oocytes were cultured for 4 h in 1.2 mM MTT and then washed several times in phenol-free RPMI medium 1640 (Sigma) supplemented with 0.5% BSA. The oocytes were then transferred into 100 ml of dimethylsulfoxide (DMSO, Sigma) in 96-well plates, and the intensity of the precipitated formazan product was assessed using a plate reader and KC Junior Software (Bio-Tek Instruments, Winooski, VT, USA).…”
Section: Discussionmentioning
confidence: 99%
“…The reaction is attributed mainly to mitochondrial enzymes and electron carriers [38,40,41], although MTT is also reduced by a number of non-mitochondrial enzymes in other cellular compartments [42]. MCN was Fig.…”
Section: Dimebon Enhanced Mtt Reduction In Both Primary Mcn and Diffementioning
confidence: 99%